Foreign policy and international financial negotiations: The external debt and the Cartagena Consensus - Jorge E. Navarrete (CEPAL Review, 1985)
The background, development and prospects of the concerted effort being made by the Latin American countries as expressed in the Cartagena Consensus and Mexico’s role in this effort are discussed in this article from a foreign policy perspective. It is neither a quantitative technical analysis of the debt problem nor a systematic review of the renegotiations of recent years and those currently in progress, Instead, an attempt is made to explore those elements of international economic performance, trade and finance which led the Latin American countries to meet at Cartagena. It goes on to analyse the basic content of the proposals made at that meeting and at Mar del Plata and Santo Domingo, to discuss how the other parties to the negotiations (governments of developed countries, international banking authorities and multilateral financial bodies) have reacted to these proposals, and, finally, to describe what the outlook for the overall Cartagena process appears to be as of mid-1985.